(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
Pinus brutia radial growth -as all wooden species- is often determined by climate, soil and physiological conditions. In order to model the relationship between radial growth of brutia pine and both of precipitation and temperature in Hir Brafa and Kfarfo forests-Tartous,10 dominant trees were selected in each forest, two perpendicular samples from each tree at breast height were taken. After samples treatment, they were cross-dated, and consequently a time series of 30 year covering the period 1982-2013 was obtained. Tree rings width were measured to the nearest 0.01 mm. The tree rings time series were standardized to remove the influence of age and forest management, by dividing measured values of rings width by smoothed ones that obtained using moving average on window of 5 years. Models were developed using the step wise method of multiple linear regression. As results, 5 models were constructed in Hir Brafa, and 2 models in Kfarfo. Spatial cross-validation was used and many statistical tests were applied to validate models developed. Results showed that, one of the two models constructed for Kfrfo forest were chosen as the best one among the tested models. It is recommended to develop more regression models for further conifers species and other tree species which are of importance in Syria. يتحدد النمو الشعاعي لأشجار الصنوبر البروتي, كما هو الحال عند بقية الأنواع الخشبية بشكل عام, بالعوامل الفيزيولوجية و التربة و المناخ. وبهدف نمذجة العلاقة بين سماكة حلقات النمو السنوية لدى الصنوبر البروتي وبيانات الهطل ودرجة الحرارة في غابتي حير برفة وكفرفو في محافظة طرطوس, تم تحديد عشرة أشجار سائدة في كل موقع.أخذت من كل شجرة سبرتان متعامدتان على ارتفاع الصدر. وبعد معاملة السبرات والقيام بعملية التأريخ البينيCross-dating حصلنا على سلاسل زمنية لحلقات النمو تمتد للفترة 1982-2013م, تم قياس سماكة حلقات النمو بدقة 0.01 ملم, ومن ثم تم تحويل قيم سلاسل حلقات النمو إلى قيم معايرة لاستبعاد تأثير العمر وعمليات التربية في النمو، وذلك بقسمة القيم المقاسة لسماكة حلقات النمو على القيم المقدرة بواسطة المتوسط المتحرك المحسوب على نافذة مقدارها/5/ سنوات. لنمذجة العلاقة بين حلقات النمو والمناخ استخدم نموذج الانحدار الخطي بالطريقة التدريجية. في النتيجة تم الحصول على خمسة موديلات رياضية في غابة حير برفة وموديلين في غابة كفرفو, وبعد إجراء الاختبار المكاني المتصالب وحساب مؤشرات جودة الموديل لكل الموديلات, تم اختيار أحد الموديلين المطورين في غابة كفرفو كأفضل موديل بين العلاقات المختبرة. توصي الدراسة بتطوير موديلات رياضية من نوع الانحدار لأنواع الصنوبريات والأنواع الحراجية الأخرى التي تشكل جزءاً مهماً من الثروة الحراجية في بلادنا.